Growth performance of roselle (Hibiscus sabdariffa) under application of food waste compost and Fe3O4 nanoparticle treatment - Hollena, Nori; Shuhaimi, Shahnaz Ad-Din; Kanakaraju, A/P Devagi (Springer Nature Switzerland, 2019)
Purpose Utilization of food waste as composting materials offers a sustainable solution to manage waste and reduce reliance on fertilizers. Method This study is focused on the efficiency of food waste compost and the effect of the addition of magnetite (Fe3O4) nanoparticles on the growth and heavy metals uptake by roselle (Hibiscus sabdariffa) for the cultivation period of 127 days. Five different treatments were applied, namely soil (S), food waste compost (F), a mixture of soil and Fe3O4 (SM), a mixture of soil and food waste compost (SF), and a mixture of soil, food waste compost, and Fe3O4 (SFM). Results After 127 days of cultivation, the plant height averaged at 803 mm with 26 leaves produced across all treatments. Total leaf area, fruit production, and biomass yield were different (P < 0.05) among the treatments. Roselle crops grown under soil and food waste (SF) media produced the highest yield (12.15 g/plant), the most number of fruits (11 fruits/plant), and the highest leaf area (1200 cm2/plant). The accumulation of heavy metals in plant tissues was lower than the toxicity levels. There was no difference in the heavy metal content in all growing media, except for Ni, Mn, and Pb. Roselle crops applied with Fe3O4 showed no difference (P > 0.05) from its control (without Fe3O4) in relation to growth performance. Conclusion The findings of this study showed that food waste can be applied in composting to promote plant growth. Therefore, it can be considered as a substitute for chemical fertilizers. Meanwhile, the application of Fe3O4 appeared to be experimental-condition dependent.